2022
DOI: 10.3390/cells11030437
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal Protease(s) and the Activation of SARS-CoV-2 Spike (S) Protein

Abstract: In this contribution, we report on the possibility that cryptococcal protease(s) could activate the SARS-CoV-2 spike (S) protein. The S protein is documented to have a unique four-amino-acid sequence (underlined, SPRRAR↓S) at the interface between the S1 and S2 sites, that serves as a cleavage site for the human protease, furin. We compared the biochemical efficiency of cryptococcal protease(s) and furin to mediate the proteolytic cleavage of the S1/S2 site in a fluorogenic peptide. We show that cryptococcal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…We don't know if a LP had been performed on the 8 dead patients not treated with amphotericin B+ flucytosine, Cryptococcus would have been found in CSF. Some authors investigated the role of cryptococcal protease during SARS-CoV-2 infection, suggesting the possible role of protease, ureases, phospholipases released by Cryptococcus in activating the SARS-CoV-2 S protein leading to hyper-inflammatory response [49]. This could explain the high mortality we found in our review.…”
Section: N Resultsmentioning
confidence: 70%
“…We don't know if a LP had been performed on the 8 dead patients not treated with amphotericin B+ flucytosine, Cryptococcus would have been found in CSF. Some authors investigated the role of cryptococcal protease during SARS-CoV-2 infection, suggesting the possible role of protease, ureases, phospholipases released by Cryptococcus in activating the SARS-CoV-2 S protein leading to hyper-inflammatory response [49]. This could explain the high mortality we found in our review.…”
Section: N Resultsmentioning
confidence: 70%
“…These syndromes are the and Cryptococcus spp. is the possible role of proteases produced by the fungus as facilitating agents of viral infection through the activation of the SARS-CoV-2 spike protein (MJOKANE et al, 2021;MJOKANE et al, 2022). Although this evidence is only proven in vitro experiments, the worsening of the general condition of patients with long-term COVID-19 in co-infection by the two pathogens may be related to this physiochemical process.…”
Section: Resultsmentioning
confidence: 99%
“…The idea of a fungal protease activating a viral substrate has been shown before. In their work, Mjokane and co-workers showed that the fungus Cryptococcus neoformans secretes protease(s) that can activate the spike protein of SARS-CoV-2 [ 35 ]. As a mimetic peptide may not fold in a similar manner as a full-length peptide, it was imperative to show if the A. fumigatus supernatant contained a protease(s) that could transduce a laboratory cell line following the activation of the SARS-CoV-2 spike protein.…”
Section: Discussionmentioning
confidence: 99%
“… A. fumigatus alkaline protease 1 (PDB ID: AFUA_4G11800) Serine-based Aspergillus fumigatus Help to disrupt the host structural barriers [ 14 ]. Suggested to act on the furin cleavage site within the S1/S2 site [ 35 ]. …”
Section: Methodsmentioning
confidence: 99%